Testing the theory of multitasking : evidence from a natural field experiment in Chinese factories - Hong, Fuhai (2019)
Using a natural field experiment with factory workers where we introduce a quantity-based performance-pay scheme in addition to their base salary, we quantify the impact of one-dimensional monetary incentives on both incentivized (quantity) and non-incentivized (quality) dimensions of output. While the management typically observes only quantity, we also observe quality by hiring quality-inspectors unbeknownst to the workers. While some workers receive a flat-rate base salary, others receive a piece-rate base salary. We find sharp evidence that workers under a flat-rate base salary trade off quality for quantity. Interestingly, this quantity-quality trade-off is statistically insignificant for workers under a piece-rate base salary. This variation in the treatment effect is consistent with a simple theoretical model that predicts that when agents are already incented at the margin, the quantity-quality trade-off resulting from additional incentives will be less prominent.